Collective organisation and external regulation of professional rugby league in the United Kingdom - O'Leary, Leanne (Trinity College (Dublin, Ireland). School of Law, 2010)
This thesis examines the external regulation of professional rugby league in the United Kingdom. It considers specifically the employment of players in the Super League competition by British clubs. In the course of this research interviews with thirty stakeholders in the industry (including: the Rugby Football League; Super League clubs; Championship clubs; professional players; sports agents; professional coaches; the Rugby League Players' Association; and a sponsor) were conducted and statements from these interviews are incorporated throughout the thesis in support of the arguments presented.
Keywords: Law, Ph.D.; Ph.D. Trinity College Dublin.